A Case of Ischemic Monomelic Neuropathy following Endovascular Arteriovenous Fistula Creation and Assisted Maturation - Sonnabend, Kyle; Park, Simon; Shah, Ketan; Lipnik, Andrew J.; Niemeyer, Matthew M. (Seminars in Interventional Radiology, 2023)
Dialysis access steal syndrome (DASS) is a phenomenon known to occur following creation of an arteriovenous fistula or arteriovenous graft. The clinical presentation of DASS is characterized by symptoms of limb ischemia due to diversion of arterial flow from the distal extremity. Ischemic monomelic neuropathy (IMN) is a rare subtype of DASS classically described as an acute, isolated presentation of peripheral neuropathy following dialysis access creation. Although the underlying pathophysiology is not entirely understood, the clinical manifestation of IMN is often described as severe distal limb pain that progresses to motor and sensory defects. The onset of IMN may occur immediately following dialysis access creation or intervention. Here, we present a case of IMN following assisted maturation of an endovascular fistula.
Keywords: ischemic monomelic neuropathy; dialysis access steal syndrome; arteriovenous fistula